Planning and managing a multi-component, multi-category international biosphere reserve: the case of the La Amistad/Talamanca range/Bocas de Toro wildlands complex of Costa Rica and Panama - Morales, R.; Barborak, J.R.; MacFarland, C. (UNESCO, París (Francia) PNUMA, Nairobi (Kenia), 2014)
Ilus. 1 ref. Sum. (En)